Changes in functional, anatomical and optical parameters of the eye in children with habitually excessive accommodation stress and pseudomyopia after regular badminton playing - E. P. Tarutta; N. A. Tarasova; G. A. Markosian; S. V. Milash; S. G. Harutyunyan; K. A. Ramazanova; N. L. Cherednichenko (Российский офтальмологический журнал, 2019)
Purpose. To study the state of refraction, accommodation, and blood flow in eye vessels of children with habitually excessive accommodation stress (HEAS) and pseudomyopia practicing badminton.Material and methods. The study involved 11 patients (20 eyes) aged 7 to 11 years (average M±SD: 9.24 ± 1.06 years) with pseudomyopia and HEAS: 4 patients with myopia (7 eyes), 3 children with hyperopia (6 eyes), 4 children with emmetropia (7 eyes) before they started practicing badminton and after playing it for a certain time. All patients were tested for visual acuity, subjective and objective accommodation, optical biometry, aberrometry, velocity of blood flow in eye vessels, and choroidal thickness.Results. After 1 year of regular badminton workout, the subjects revealed a 0.92 ± 0.82 D weakening of manifest refraction, a decrease in accommodation tone by 0.85 ± 0.77 D, an increase in blood flow rate in ophthalmic artery and the central retinal artery, an increase in positive spherical aberration, a decrease in aberrations associated with mismatch and irregularity ofoptical system elements (tilt, trefoil, coma), which indirectly indicates a strengthening of the ligamentous apparatus of the lens.Conclusion. Practicing sports (badminton) contributes to the elimination of pseudomyopia, improvement of uncorrected visual acuity, accommodative ability, and ophthalmic hemodynamics indicators.